Using tomography images to study the mixing of wheat straw slurries. Issue 4 (3rd July 2016) - Movafagh, Hiva; Turcotte, Ginette; Ein-Mozaffari, Farhad
ABSTRACT: Wheat straw is a good renewable source for the production of bioethanol. However, the mixing of wheat straw slurry is a challenging task due to its complex rheology. This type of slurry behaves as a non-Newtonian fluid possessing a yield stress. In mixing operations, the presence of a yield stress creates a region of active motion (cavern) around the impeller and stagnant zones in the remainder of the vessel. In this paper, electrical resistance tomography (ERT) was employed to measure the dimensions of the cavern around the impeller as a function of the wheat straw concentration, fiber size, impeller speed, and impeller type. These data were then utilized to estimate the yield stress of wheat straw slurries. To test the accuracy of this technique, the yield stress of a xanthan gum solution calculated from the tomography method was compared to that achieved using a rheometer. This study is the first novel application of ERT to estimate the yield stress of wheat straw slurries, as opposed to directly measuring it using rheometry. Average yield stresses of 5, 7, and 10 wt% slurries were found to be 1.31 Pa, 4.2 Pa, and 14.8 Pa, respectively, for fiber size of ≤ 2 mm, and 3.4 Pa, 6.8 Pa, and 16.7 Pa, respectively, when fiber size was 8 mm.